Learning of geometric and spatial-orientation concepts, through play, in Early Childhood Education (Edma 0-6: Educación Matemática en la Infancia, 2021)
This work focuses on justifying and promoting the use of games in Early Childhood Education classrooms as a didactic resource for learning mathematical concepts and, in particular, basic geometric figures and bodies and the main spatial notions. In the first part, the importance of play in childhood is argued, not only as a recreational activity, but also as a means of learning. This strategy, in addition to producing fun and entertainment for students, is useful and effective for learning mathematical concepts in a meaningful way. In the second part, we present a didactic proposal, for students between the ages of three and five, whose activities aim to favor the understanding and integration of these mathematical notions while working in an active, participatory and motivating way.
Keywords: Early Childhood Education; Game; Significant learning; Geometry; Spatial orientation